Patho-histological features of fibroblastic sarcoid in horses - Portenko, M.; Shchebentovska, O. (Regulatory Mechanisms in Biosystems, 2022)
Sarcoid is one of the most common skin tumours, which is diagnosed in various breeds of horses at any age regardless of the animal’s sex. Such fibroblastic neoplasm manifests itself in several clinical ways with its specific morphological features. As a rule, it metastasizes rarely but can be locally invasive. The disease’setiology is multifactorial and includes the confirmed role of the bovine papillomavirus and genetic and environmental factors. The article introduces the results of a retrospective study of horses of the Ukrainian riding breed with a fibroblastic sarcoid type, which was localized mainly in the area of the external thoracic vein. Neoplasms were represented by two types. The first one included broad base neoplasms without a pronounced pedicle but with signs of hyperkeratosis. Massive rounded dense formations with an ulcerated surface refer to the second type. To verify the studied types of sarcoid, wide surgical excision of the lesion’svisible parts was performed, followed by the selection of fragments for the pathohistological diagnosis. Also, additional staining methods were used to detect the connective and muscle tissue (Van Gieson’s staining) and elastic fibers (Weigert’s resorcin-fuchsin staining). Microscopically, the neoplasm without a visible pedicle showed signs of hyperkeratosis and acanthosis in the peritumoral epidermal layer. Epidermis desquamation with a significant amount of oxyphilic detritus, diapedesis hemorrhages, and dilated vessels was also detected in some areas. Chaotic placement of fibroblasts and fibrocytes was noted, to a greater extent, subdermally. Anisocytosis and anisokaryosis were expressed moderately. Sarcoids, macroscopically presented in the form of massive dense formations with an ulcerated surface, were histologically characterized by the replacement of the epidermis with cellular elements, subdermal hemorrhages, and the characteristic perpendicular orientation of coarse collagen fibers towards the basement membrane. Closely spaced spindle-shaped cells with fibers forming moiré structures were visualized in the deep dermis layers. Nuclei were hyperchromic and elongated in shape, no atypical mitoses were noted. Pathohistological examination during the identification of a sarcoid type for diagnostic purposes can cause rapid growth and formation of an ulcer. The final diagnosis regarding equine sarcoid can be made based on a combination of clinical signs, histopathological examination, and molecular genetic testing with the isolation of BPV DNA.